Development of a Sildenafil Citrate Microemulsion-Loaded Hydrogel as a Potential System for Drug Delivery to the Penis and Its Cellular Metabolic Mechanism - Apichart Atipairin; Charisopon Chunhachaichana; Titpawan Nakpheng; Narumon Changsan; Teerapol Srichana; Somchai Sawatdee (MDPI AG, 2020)
Sildenafil citrate is used to treat mild to moderate erectile dysfunction and premature ejaculation. However, it has low oral bioavailability, numerous adverse effects, and delayed onset of action. These problems may be resolved by transdermal delivery to the penis. Hence, sildenafil citrate was formulated as a microemulsion system using isopropyl myristate, Tween 80, PEG400, and water (30:20:40:10). The hydrogel used in the microemulsion was 2% w/w poloxamer 188. The sildenafil microemulsion-loaded hydrogels were characterised for their appearance, particle size, pH, spreadability, swelling index, viscosity, sildenafil drug content, membrane permeation, epithelial cell cytotoxicity, and in vitro drug metabolism. The optimised formulated microemulsion showed the lowest droplet size and highest solubility of sildenafil citrate. The in vitro skin permeation of the sildenafil citrate microemulsion-loaded hydrogel was significantly higher than that of the sildenafil suspension, with a 1.97-fold enhancement ratio. The formulated microemulsion exhibited a 100% cell viability, indicating its safety for skin epithelial cells. The major metabolic pathway of sildenafil citrate loaded in the microemulsion formulation was hydroxylation. Furthermore, loading sildenafil in the microemulsion reduced the drug metabolite by approximately 50% compared to the sildenafil in aqueous suspension. The sildenafil citrate-loaded isopropyl myristate-based microemulsion hydrogels were physically and chemically stable over 6 months of storage. The sildenafil citrate microemulsion-loaded hydrogel showed in vitro results suitable for used as a transdermal drug delivery system.